2009
DOI: 10.1182/blood-2008-04-149070
|View full text |Cite
|
Sign up to set email alerts
|

The largest prospective warfarin-treated cohort supports genetic forecasting

Abstract: Genetic variants of cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase (VKORC1) are known to influence warfarin dose, but the effect of other genes has not been fully elucidated. We genotyped 183 polymorphisms in 29 candidate genes in 1496 Swedish patients starting warfarin treatment, and tested for association with response. CYP2C9*2 and *3 explained 12% (P ‫؍‬ 6.63 ؋ 10 ؊34 ) of the variation in warfarin dose, while a single VKORC1 SNP explained 30% (P ‫؍‬ 9.82 ؋ 10 ؊100

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
376
4
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(408 citation statements)
references
References 49 publications
(92 reference statements)
19
376
4
9
Order By: Relevance
“…17 A review by Schelleman et al 18 illustrates the large number of CYP2C9*2 and *3 allele frequency studies that have focused on populations of European ancestry, in which these genetic variants are common. Together they have been found to account for 12 10 to 18% 6 of the variation in warfarin dose. Recent research has identified a third gene, CYP4F2 as influencing an individual's sensitivity to warfarin.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…17 A review by Schelleman et al 18 illustrates the large number of CYP2C9*2 and *3 allele frequency studies that have focused on populations of European ancestry, in which these genetic variants are common. Together they have been found to account for 12 10 to 18% 6 of the variation in warfarin dose. Recent research has identified a third gene, CYP4F2 as influencing an individual's sensitivity to warfarin.…”
Section: Introductionmentioning
confidence: 92%
“…Genetic factors have also been shown to affect warfarin maintenance. 3,10 Previous studies have demonstrated that two genes, VKORC1 and CYP2C9, which are involved in the vitamin K-dependent clotting pathway, explain an additional 30-54% of variance observed in warfarin dosing. 6,9,11 Warfarin exists as a mixture of two stereoisomers, R and S. 8,12 S-warfarin is approximately three times as active as the R-enantiomer 12 and works by antagonizing the vitamin K-dependent clotting pathway.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Il faut donc définir la dose à l'équilibre pour chaque patient afin d'obtenir une bonne efficacité thérapeu-tique avec un risque hémorragique minimum. Après des recherches à l'aide des approches gène-candidat, les polymorphismes des gènes codant pour le cytochrome P4502C9 (CYP2C9), la vitamine K époxyde réductase (VKORC1) [29] et le cytochrome P4504F2 (CYP4F2) ont été significativement associés à la variabilité de réponse à la warfarine par des approches de génomique (genome-wide) [9][10][11]. Ainsi, les génotypes de CYP2C9, de VKORC1 et de CYP4F2, l'âge et le poids permettent d'expliquer 60,5 % de la variabilité interindividuelle de la dose à l'équilibre de la warfarine [12].…”
Section: Les Mécanismes Physiopathologiques Des Réactions Idiosyncratunclassified